Online communities on competing platforms: Evidence from game wikis - Loh, Johannes; Kretschmer, Tobias (Strategic Management Journal, 2023)
Research Summary Many platforms rely on volunteer contributions for value creation. Thus, unpaid contributors are valuable to the platform, but control over their activities is limited. We study whether and how volunteer communities can provide a competitive advantage and ask how contributor behavior depends on a platform's competitive position. We propose two channels: First, a stronger competitive position facilitates contributor coordination , leading to a larger active community. Second, a platform's competitive position is related to contributor motivation , which drives how much individuals contribute. Studying two competing game wiki platforms, we find that a platform's stronger competitive position is associated with higher activity, primarily driven by the number of contributors, which in turn triggers increased contributions by existing contributors. Further, high‐productivity contributors are especially active on a stronger platform. Managerial Summary Online “crowdsourcing” communities create value for many digital platforms, but managing them in a way that ensures productive contributions is challenging. To better understand the conditions under which online communities create value productively we analyze how contribution patterns differ between more and less successful platforms. We study 13 game wiki communities on two competing platforms and find that success is tied to higher activity, which is in turn the result of more manpower in the value creation process, but also higher productivity by individual contributors. In addition, a dedicated core of highly productive community members is an important driver of platform success. These findings have implications for the motivation of community members, and the entry and growth strategies of crowdsourced platforms.